The Epididymis as a Target for Toxicants - De Grava Kempinas, W. [UNESP]; Klinefelter, G. R. (Elsevier, 2010)
The epididymis is the organ in which sperm mature by developing the capacity for progressive motion and fertilizing ability. There is evidence that sperm quality in humans and other animals has diminished, in parallel with increased adverse trends in male reproductive health such as testicular cancer, cryptorchidism, and hypospadia. It is speculated that these events may have manifested from changes in environmental influences that have presented over the past 50 years. It is reasonable to assume that if semen quality is declining in men around the world, it may be at least in part due to environmental factors that compromise the process of epididymal sperm maturation. However, sperm maturation itself is a complex and poorly understood process that involves, in addition to other things, plasma membrane modifications which result in the capacity for progressive motility and the acquisition of fertilizing ability. Sperm quality may also be compromised by acceleration of sperm transit time throughout the epididymal duct, as the time available for acquisition of fertility would be reduced. Moreover, accelerated transit could reduce the number of sperm available for ejaculation. Toxicology of the epididymis is a relatively new facet of male reproductive toxicology. Research in this field is inherently difficult because to identify toxicant-induced alterations in the structure and function of the epididymis it is necessary to control experimentally for any confounding factors, such as testicular lesions produced by the agent. For this, unique in vivo and in vitro methodologies need to be developed and applied. Studies on the toxicology of the epididymis not only elucidates exposures that target this organ, but fosters a better understanding of the normal structure and function of the organ. This could possibly benefit the treatment of certain idiopathic infertile men, as well as lead to the development of novel, nonhormonal male contraceptives that irreversibly target sperm maturation rather than the process of spermatogenesis.
Keywords: Biomarker of fertility; Epididymis; Sperm quality; Sperm transit time; Toxicology